(untitled) (Journal of Pakistan Orthopaedic Association, 2020)
We live in an amazing world at amazing times as we are in the evolutionary stages of Orthobiologics. Now we are increasingly looking for biological solutions of biological problems and the best news is that it has gone from science fiction to a very real entity. Similarly access to investigations for previously impossible tasks have become a reality. Imagine a scenario when one is playing sports and hurts his shoulder and we would like to investigate him after a thorough clinical assessment. We would like to order a Magnetic Resonance Imaging (MRI) to exclude soft tissue injuries and we run into a well as the patient is claustrophobic, has a pacemaker or is overweight or has metal inside his body.1,2 Although clinical examination and MRI play a key role in diagnosis, sometimes interpretation can be unclear or even wrong.3,4 Nothing is more accurate than direct visualization, particularly when we have to determine if the patient need surgery.5,6With forward thinking and innovation technology there is now a real solution Office -Based Needle Arthroscopy.7 It is a small Gadget that will make a Big Difference to the clinical practice.8 (Fig IA, IB, IC, ID) Clinic or of?ce based arthroscopy is by no means a new idea but it has previously failed to become widely used. This is probably due the dif?culties in transferring the type of required equipments (which closely mirrored that used in operating theatres) to the clinic environment.